The Development of Speaking Skills in English Language Lessons - Danica Gondova (Communications - Scientific letters of the University of Zilina, 2012)
The paper deals with the importance of teaching speaking skills in foreign language lessons and it compares theoretical backgrounds and objectives of language teaching with the reality observed at some primary and lower-secondary schools and gymnasia in the Zilina Region. It also presents the results of the research which prove that in the observed lessons, speaking skills were not developed sufficiently.